2017
DOI: 10.1093/infdis/jix529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV on the Frequency and Number of Mycobacterium tuberculosis–Specific CD4+ T Cells in Blood and Airways During Latent M. tuberculosis Infection

Abstract: Human immunodeficiency virus infection leads to lower frequencies of CD4+ T cells specific for Mycobacterium tuberculosis in blood and lungs. However, an influx of T cells to the lungs results in similar absolute numbers of specific CD4+ T cells, compared with uninfected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
(45 reference statements)
4
23
0
Order By: Relevance
“…This latter phenomenon has also been observed during Mtb/SIV infection in macaques [48]. It is important to understand how HIV directly affects granulomas as responses in PBMC, BAL, and granulomas are not well correlated, as observed in this study and others [11,12,14,15,43].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This latter phenomenon has also been observed during Mtb/SIV infection in macaques [48]. It is important to understand how HIV directly affects granulomas as responses in PBMC, BAL, and granulomas are not well correlated, as observed in this study and others [11,12,14,15,43].…”
Section: Discussionsupporting
confidence: 58%
“…We did not find overt PBMC immune responses that correlated with reactivation in either the Mtb/αCD4 or Mtb/SIV groups. HIV/Mtb co-infection clinical studies have demonstrated that HIV preferentially induces an overall reduction in Mtb-specific PBMC production of IL-2 producing PLOS PATHOGENS peripheral CD4 T cells [41], Mtb-specific IL-17 and Th1 producing cytokines from T cells [42][43][44][45], and Th transcription factors (e.g., FoxP3, T-bet) within Mtb-specific CD4 T cells [46]. In one study, 5 patients with newly acquired HIV infection and LTBI were found to have reduced frequencies of Mtb-specific CD4 T cells though none developed reactivation in the first year of seroconversion [41].…”
Section: Discussionmentioning
confidence: 99%
“…Progressive depletion and dysfunction of CD4 T-cells following HIV infection leads to immune suppression and negatively impacts immunity to M. tuberculosis . Specific depletion of M. tuberculosis -specific CD4 T-cells has been reported in the peripheral blood(15, 16) and broncheoalveolar lavage (BAL) samples(17, 18) of HIV-infected individuals with LTBI. Several studies indicate that specific depletion may be a consequence of enhanced HIV co-receptor expression in CD4 T-cells, particularly CCR5, in TB patients(15, 1924).…”
Section: Immunopathogenesis Of Tuberculosis In Humans and Animal Modelsmentioning
confidence: 99%
“…It has recently been shown that the activation profile of Mtb-specific CD4 + T cells as assessed by the expression of CD38, HLA-DR, and Ki-67 reflects TB disease in both HIV infected and uninfected individuals ( 24 ). It is interesting to speculate that expression of caspase-3 in Mtb-specific CD4 + T cells from HIV-infected ATB patients will be similarly higher compared to HIV infected individuals with LTBI despite the reduction of peripheral CD4 + T cells during HIV infection ( 25 , 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%